2006
DOI: 10.1111/j.1365-2222.2006.02628.x
|View full text |Cite
|
Sign up to set email alerts
|

Does skin prick test reactivity to purified allergens correlate with clinical severity of peanut allergy?

Abstract: Ara h 2 and Ara h 6 appeared to be more potent than Ara h 1 and Ara h 3. Both SPT reactivity to low concentrations of Ara h 2 and Ara h 6 and to higher concentrations of Ara h 1 and Ara h 3 were shown to be indicative of severe symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 32 publications
3
107
1
Order By: Relevance
“…This would require clinical investigations, studies in validated animal models, or in cell-based ex-vivo methods, all of which are beyond the scope of the current study. Nevertheless, a clinical study carried out by Peeters et al has shown that Ara h 2 and Ara h 6 are the most potent peanut allergens (Peeters et al, 2007), and our observation that the levels of these particular allergens do not differ substantially between the peanut types suggests that the in vivo allergenicity of the peanut types will also be comparable.…”
Section: Consequences For Allergenicitymentioning
confidence: 77%
See 1 more Smart Citation
“…This would require clinical investigations, studies in validated animal models, or in cell-based ex-vivo methods, all of which are beyond the scope of the current study. Nevertheless, a clinical study carried out by Peeters et al has shown that Ara h 2 and Ara h 6 are the most potent peanut allergens (Peeters et al, 2007), and our observation that the levels of these particular allergens do not differ substantially between the peanut types suggests that the in vivo allergenicity of the peanut types will also be comparable.…”
Section: Consequences For Allergenicitymentioning
confidence: 77%
“…A clinical study applying skin-prick tests demonstrated that peanut allergens Ara h 2 and Ara h 6 are 100-to 1000-fold more potent than Ara h 1 and Ara h 3 (Peeters et al, 2007), and it is therefore important to closely evaluate Ara h 2 and Ara h 6 specifically. Even though these allergens are less abundant (around 6% each, together approximately 12% of the total protein in peanut) compared to Ara h 1 and Ara h 3 (about 17% and 71%, respectively; Table 1), they may dominate the allergenic potential of peanut protein.…”
Section: Quantification Of Major Allergens Ara H 1 Ara H 2 Ara H 3mentioning
confidence: 99%
“…However, only a few comparative SPT studies with purified food allergens have been conducted, [28], [72], [73] and [74] which is mainly due to the high demands of approval in clinical trials as requested by the institutional review boards and regulatory authorities to ensure patient safety (test allergens have to be licensed as biotechnologic products). These few studies verified a superior diagnostic potential of recombinant allergens.…”
Section: Skin Tests With Purified Allergenic Moleculesmentioning
confidence: 99%
“…This was confirmed by doubleblind placebo-controlled oral challenge and the authors concluded that this was not due to a primary sensitization, but due to cross-reactivity with aero-allergens. Lupin was introduced into the food chain in the late nineties in the EU (Peeters et al, 2007). According to Hieta et al (2009), allergic reactions to lupin occurred most frequently among patients with other food allergies, mainly to legumes, indicating that lupin allergy occurs largely due to cross-reactivity.…”
Section: Allergenicity Risk Assessmentmentioning
confidence: 99%
“…According to Hieta et al (2009), allergic reactions to lupin occurred most frequently among patients with other food allergies, mainly to legumes, indicating that lupin allergy occurs largely due to cross-reactivity. However, others showed that lupin allergy is not always due to cross-reactivity, but can be the result of primary sensitization through oral exposure (Lindvik et al, 2008;Peeters et al, 2007), and also by prior inhalation of lupin flour (Prieto et al, 2010). Similar to lupin, kiwi fruit was introduced to the EU in the 20th century and soon after kiwi allergy was first reported (Fine, 1981).…”
Section: Allergenicity Risk Assessmentmentioning
confidence: 99%